BUDGET REALIZATION ANALYSIS AND PROVISION OF INCENTIVES FOR HEALTH WORKERSAT THE HEALTH OFFICE OF NORTH SULAWESI PROVINCE - Kethlin Carolin Mewo; Steven V. Tarore; Laurens L. Bulo (PT. Radja Intercontinental Publishing, 2026)
This study aims to analyze the incentive provision procedures and the determinants that influence them. The type of research used is qualitative with a descriptive-analytical approach. Informants in this study consisted of the Head of the General Sub-Section, the Commitment Making Officer (PPK), the expenditure treasurer, the incentive program manager, administrative staff, and health workers receiving incentives. Data were obtained through in-depth interviews, observation, and documentation. Then, they were analyzed through data reduction, data presentation, and conclusion drawing. Their validity was tested through credibility, transferability, dependability, and confirmability tests. The results showed that the incentive provision procedures include data collection, setting cost standards, implementing SOPs, verification and validation, and budgeting and disbursement of funds. However, their implementation has not been optimal due to delays in data submission, administrative inconsistencies, limited human resource capacity, low budget realization, and suboptimal coordination between work units, which have resulted in delays in incentive payments. Therefore, it is necessary to improve the quality of administration, apparatus capacity, coordination, and optimize budget realization.